Doping in the Ultimate Fighting Championship (UFC): A 4‐year epidemiological analysis. Issue 4 (22nd December 2020) - Fares, Mohamad Y.; Baydoun, Hasan; Salhab, Hamza A.; Khachfe, Hussein H.; Fares, Youssef; Fares, Jawad; Abboud, Joseph A.
Abstract: Background: Doping is a practice that is present in many sports and organizations, including mixed martial arts and the Ultimate Fighting Championship (UFC). The aim of this study is to explore the epidemiological patterns of doping among UFC athletes. Methods: We screened the official United‐States‐Anti‐Doping‐Agency® (USADA) website, the annual USADA reports and the official UFC website for information on fighters and anti‐doping rule violations (ADRVs). Our dataset included gender, age, weight class, testing numbers, date of ADRV, type of ADRV, and duration of suspension. Appropriate statistical tests were conducted to assess for statistical significance. Results: USADA tested 1070 UFC athletes 2624 times as of late 2015 up till the end of 2019 ( N = 1070). A total of 209 adverse findings were recorded; out of which, 102 ADRVs were committed by 93 athletes (8.7%) from all weight divisions. This constituted an adverse finding rate of 16.55 per 1000 test and an ADRV rate of 8.08 per1000 test. Mean age of sanctioned athletes was 32 years. Use of anabolic steroids was significantly the most common ADRV recorded ( p = 0.018). The men's heavyweight division had an ADRV rate of 19.3 per 1000 tests, significantly higher than that of women's bantamweight division at 2 per 1000 tests ( p = 0.03), women's featherweight division at 0 per 1000 tests ( p = 0.009), and men's flyweight division at 3 per 1000 tests ( p = 0.035). ADRV rate showed a significantly increasing trend among men's weight divisions ( p < 0.001). Conclusion: Doping is present in mixed martial arts. Increasing testing numbers, raising awareness and education on the risks of doping, and conducting further research on the issue is key to help resolve this problem. Abstract : A total of 1070 athletes were tested 12, 646 times, out of which 102 violations were committed by 93 athletes. Our study showed that weight is a significant variable with respect to doping violations, in particular among male fighters. In addition, anabolic steroids were found to be significantly the most commonly used banned substance in the Ultimate Fighting Championship.